OPTIMIZING THE TAX RISK OF PROFIT TAX THROUGH TAX CONTROL - Yangieva Nargiza Saidkulovna (Scholar Express Journal, 2025)
This article is devoted to the analysis of the issues of optimizing tax risk for profit tax through tax control.
Keywords: Tax risk; tax control; tax risks